Preparing for Brexit - McGowan, Lee. author. aut Link
IX, 133 p. 1 illus.
Keywords: This book studies the developments of the Brexit process between June 2016 and June 2017. The British electorate’s decision to leave the European Union in June 2016 marks a major point in post war British politics, for it overturns the core policy of all preceding British governments since the early 1960s. The referendum brought down one Prime Minister, David Cameron, and bequeathed to his successor, Theresa May, the considerable challenge of negotiating the UK’s departure from the EU. The magnitude of the task is colossal. While the time frame to secure the terms of the exit is short, the exact form of Brexit remains unclear to this day. With this book the author sets the context for the negotiations. He introduces the actors and the negotiating teams and highlights the key issues and considerations of both sides. While some works just focus on the interplay between Brussels and London, neglecting the internal regional dimension and the role and interests of the devolved administrations in the negotiations, the author looks specifically at Northern Ireland, the part of the UK that will be affected most by Brexit – in terms of both its economic and political significance. The book concludes with consideration of the impact of the 2017 general election on the negotiations. It will be of interest to students, scholars, policy makers and the wider reader interested in British politics and the future of the EU.